Bayesian analysis of quantitative traits in popcorn (Zea mays L.) through four cycles of recurrent selection. (1st October 2016) - Amaral Junior, Antonio Teixeira do; Freitas, Ismael Lourenço de Jesus; Guimarães, Amanda Gonçalves; Maldonado, Carlos; Arriagada, Osvin; Mora, Freddy
Abstract: A Bayesian analysis of genetic parameters for quantitative traits was carried out in full-sib families of popcorn through four cycles ( C 5, C 6, C 7, and C 8 ) of recurrent selection. The parameters of Bayesian model were estimated using the independence chain algorithm. Grain yield and plant height were found to be moderately heritable ranging from 0.25 to 0.48 and 0.45 to 0.58, respectively. The highest heritability estimates were found for popping expansion volume at C 5 ( = 0.71), and C 7 ( = 0.63). The response of recurrent selection was 30.5 and 32.3% for grain yield and popping expansion volume, respectively. In C 8, predicted genetic advances (from the Bayesian prediction of genotypic values) were 4.8, 4.3, and 2.9% for plant height, grain yield, and popping expansion volume, respectively. The significant genetic variability among popcorn families in successive cycles of recurrent selection has sustained continued genetic progress in breeding for the traits of interest.